EP.FRI.48 Right iliac fossa pain in females: more than appendixes and ovarian cysts; Haemorrhagic Cyst in the Canal of Nuck: A Case Report. (28th October 2021) - Davis, Heather; Marshall, Caitlin; Nahid, Md Abu Kamal; Shah, Ankur
Abstract: Case report: A 43-year-old woman presented with acute onset migratory right iliac fossa pain, on a background of intermittently painful right groin swelling. CT demonstrated differential diagnosis of appendicitis besides an ovarian cyst. Diagnostic laparoscopy was undertaken with a view to diagnosis and treat possible appendicitis, ovarian cyst and inguinal hernia. To our surprise, a haemorrhagic nuchal cyst was seen intraoperatively, and duly aspirated. Post-operatively she recovered well and was discharged the same day. Introduction: The Canal of Nuck is a small evagination of parietal peritoneum which accompanies the round ligament through the inguinal canal, in females. It is obliterated in the first year of life. When this remains patent, it can fill with fluid and result in the formation of cysts (akin to hydroceles in patent processus vaginalis). In current literature there are only sixteen case reports of Nuck hydroceles in adults, with only one haemorrhagic cyst reported. These are typically diagnosed in children, but occasionally present in women (aged 35.18 ± 3.27) with groin swelling and are frequently misdiagnosed as hernias. It is only when these woman are taken to theatre, that the correct diagnosis is discovered. Conclusion: This case highlights the importance of considering Canal of Nuck cysts when women present with groin swellings, to ensure quick diagnosis and appropriate management is delivered under the correct speciality.